Effect of Ru precursors and reduction conditions on catalyst performance in glycerol hydrogenolysis - Mane, R.B.; Patil, S.T.; Gurav, H.; Rayalu, S.S.; Rode, C.V. (ChemistrySelect, 2017)
Catalyst precursors, their reduction protocols and reaction conditions integrally influenced the activity and selectivity pattern in glycerol hydrogenolysis. Ru prepared from chloride precursor (Ru(Cl)/C−B) showed the maximum selectivity to C−C cleavage products EG (56 %) and methanol (17 %) with 23 % selectivity to 1,2-PDO. While, that prepared from nitrosyl precursor (Ru(n)/C−B) showed higher selectivity to 1,2-PDO (44 %) and lower to EG (42 %). The catalysts prepared either with chloride or nitrosyl precursors but reduced by H2 showed lower glycerol conversion (10-11 %) than NaBH4 reduced catalysts. For these catalysts, 1,2-PDO selectivity increased to 40–43 % along with the major formation of 2-propanol (48-49 %) and very less selectivities to C−C cleavage products. The lower activity of the H2 reduced catalysts can be related to their lower acidity and the bigger Ru metal particle size (3-5 nm). For Ru(Cl)/C−B catalyst, glycerol conversion increased from 28–97 % with a rise in temperature from 180 to 250 oC also favoring 1,2-PDO selectivity; indicating that C−O bond cleavage was favoured in comparison to C−C scission, at higher temperature.